Purified murine granulocyte/macrophage progenitor cells express a high-affinity receptor for recombinant murine granulocyte/macrophage colony-stimulating factor. - Williams, D E (1988)
Purified recombinant murine granulocyte/macrophage colony-stimulating factor (GM-CSF) was labeled with 125I and used to examine the GM-CSF receptor on unfractionated normal murine bone marrow cells, casein-induced peritoneal exudate cells, and highly purified murine granulocyte/macrophage progenitor cells (CFU-GM). CFU-GM were isolated from cyclophosphamide-treated mice by Ficoll-Hypaque density centrifugation followed by counterflow centrifugal elutriation. The resulting population had a cloning efficiency of 62-99% in cultures containing conditioned medium from pokeweed mitogen-stimulated spleen cells and 55-86% in the presence of a plateau concentration of purified recombinant murine GM-CSF. Equilibrium binding studies with 125I-labeled GM-CSF showed that normal bone marrow cells, casein-induced peritoneal exudate cells, and purified CFU-GM had a single class of high-affinity receptor with an approximate Ka of 10(8)-10(9) M-1. CFU-GM expressed an average of 3783 +/- 4 receptors per cell; normal bone marrow cells, 1518 +/- 242 receptors per cell; and peritoneal exudate cells, 2025 +/- 216 receptors per cell. Affinity crosslinking studies demonstrated that 125I-labeled GM-CSF bound specifically to two species of Mr 180,000 and 70,000 on CFU-GM, normal bone marrow cells, and peritoneal exudate cells. The Mr 70,000 species is thought to be a proteolytic fragment of the intact Mr 180,000 receptor. The present studies indicate that the GM-CSF receptor expressed on CFU-GM and mature myeloid cells are structurally similar. In addition, the number of GM-CSF receptors on CFU-GM is twice the average number of receptors on casein-induced mature myeloid cells, suggesting that receptor number may decrease as CFU-GM mature.